Response of INM in rice in rice–wheat cropping system - CHAUDHARY, KAUTILYA; TRIPATHI, H C; SINGH, KULDEEP; SHWETA, SHWETA; KUMAR, ASHOK (The Indian Journal of Agricultural Sciences, 2021)
A field experiment was carried out at the research farm of C.S. Azad University of Agriculture & Technology, Kanpur, UP during kharif of 2013-14 & 2014-15, to study the effect of INM on yield, nutrient contents and uptake of rice. The experiment was conducted with 11 treatments, viz. control, 100% NPK (RDF 120:60:40 kg/ha), 100% NPK + FYM 5 t/ha, 100% NPK + blue green algae (BGA), 100% NPK + FYM + BGA, 100% NPK + 40 kg S/ha, 100% NPK + 5 kg Zn/ha, 100% NPK + 40 kg S/ha + 5 kg Zn/ha, 100% NPK + 40 kg S/ha + 5 kg Zn/ha + 10 kg Fe/ ha, 100% NPK + FYM + BGA + 40 kg S/ha + 5 kg Zn/ha + 10 kg Fe/ha and 125% NPK in RBD replicated thrice. Results of this study revealed that among the different INM options significantly highest grain (5.27 t/ha), straw (6.23 t/ha) and biological yield (11.5 t/ha) with harvest index (45.8%) were recorded with 100% NPK + FYM + BGA + 40 kg S/ha + 5 kg Zn/ha + 10 kg Fe/ha. Application of 100% NPK increased grain yield by 100% over control and further addition of FYM at the rate of 5 t/ha increased the yield by 2.75% compared to 100% RDF. The highest protein content, starch content and head rice recovery was recorded with application of 100% NPK + FYM + BGA + 40 kg S/ha + 5 kg Zn/ha + 10 kg Fe/ha.